2016
DOI: 10.1371/journal.pntd.0004281
|View full text |Cite
|
Sign up to set email alerts
|

Long-Lasting Immune Protection and Other Epidemiological Findings after Chikungunya Emergence in a Cambodian Rural Community, April 2012

Abstract: The East/Central/South African genotype of Chikungunya virus with the E1-A226V mutation emerged in 2011 in Cambodia and spread in 2012. An outbreak of 190 cases was documented in Trapeang Roka, a rural village. We surveyed 425 village residents within 3–4 weeks after the outbreak, and determined the sensitivity and specificity of case definitions and factors associated with infection by CHIKV. Self-reported clinical presentation consisted mostly of fever, rash and arthralgia. The presence of all three clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 34 publications
(43 reference statements)
1
37
0
1
Order By: Relevance
“…CHIKF outbreaks in Southeast Asia have been markedly episodic, with long interepidemic intervals. This can be at least partially attributed to durable immunity, as suggested by serosurveys in Thailand (59), the Philippines (60, 61), and Cambodia (62). However, the recent introduction into the region of the IOL has resulted in large-scale epidemics in both Malaysia and Thailand in 2008 and 2009.…”
Section: Discussionmentioning
confidence: 99%
“…CHIKF outbreaks in Southeast Asia have been markedly episodic, with long interepidemic intervals. This can be at least partially attributed to durable immunity, as suggested by serosurveys in Thailand (59), the Philippines (60, 61), and Cambodia (62). However, the recent introduction into the region of the IOL has resulted in large-scale epidemics in both Malaysia and Thailand in 2008 and 2009.…”
Section: Discussionmentioning
confidence: 99%
“…In acute symptomatic infection, following an incubation period of approximately 3 days, there is an abrupt onset of fever, headache, rash, arthralgia, and myalgia, which typically last for 1 to 2 weeks . After this, seroconversion likely confers lifelong immunity . As well as neurological manifestations, chikungunya virus is associated with complications of the cardiovascular, renal, respiratory, hepatic, gastrointestinal, and adrenal systems, sometimes collectively referred to as “atypical features.” However, a disorder of the nervous system appears to be the most common severe complication of chikungunya infection (Table ).…”
Section: Clinical Findingsmentioning
confidence: 99%
“…Although it has been reported that a high proportion of CHIKV infections are symptomatic (80 to 97%) (1,27,(49)(50)(51), the ratio of symptomatic to inapparent CHIKV infections (S/I ratio) has varied markedly in the literature (5,27,(52)(53)(54)(55)(56). Factors associated with the S/I ratio include the presence of preexisting neutralizing antibodies to CHIKV (52,55) and patient age (52,54,56,57). Notably, both negative (54,57) and positive (52) associations between age and symptomatic infection have been reported.…”
Section: Acute Clinical Presentation and Differential Diagnosismentioning
confidence: 99%